2017
DOI: 10.1111/cns.12676
|View full text |Cite
|
Sign up to set email alerts
|

Oculomotor deficits in spinocerebellar ataxia type 3: Potential biomarkers of preclinical detection and disease progression

Abstract: This study showed that a series of neuropathological changes reflected by oculomotor abnormalities appeared preferentially in preclinical stage of SCA3. Accordingly, objective oculomotor preclinical signs may be useful to detect the optimum time-point for therapeutic interventions in future clinical trials of SCA3. Larger and longitudinal data are warranted to confirm our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 30 publications
1
39
0
Order By: Relevance
“…These studies reported that brainstem oculomotor signs (67.9%) were the most common in their cohort of SCA3 patients (13, 14). However, brainstem oculomotor signs were less frequent (23.5%) in our SCA3 group, which was supported by another study in Chinese SCA3 patients (25). Previous studies have shown that oculomotor alterations could be detected in the preclinical stage of SCAs (26).…”
Section: Discussionsupporting
confidence: 89%
“…These studies reported that brainstem oculomotor signs (67.9%) were the most common in their cohort of SCA3 patients (13, 14). However, brainstem oculomotor signs were less frequent (23.5%) in our SCA3 group, which was supported by another study in Chinese SCA3 patients (25). Previous studies have shown that oculomotor alterations could be detected in the preclinical stage of SCAs (26).…”
Section: Discussionsupporting
confidence: 89%
“…Oculomotor characteristics are recognized as distinguishing features among SCAs. Slow saccades is a key feature of SCA2 and could be detected in SCA3 but usually in late stage in our cohort (Wu et al, ). We found a mild reduced horizontal saccade velocity in both Patients 1 and 2, which could be the effect of the CAG expansions in ATXN2 , or just a coincidence of the phenotypic heterogeneity in SCA3 alternatively.…”
Section: Discussionmentioning
confidence: 55%
“…To measure the severity of ataxia, we used the Scale for the Assessment and Rating of Ataxia (SARA) that has been validated. Eye movements were recorded using video‐oculography following a central oculomotor battery that we described before (Wu et al, ). AAO was determined by a structured interview in which the patient and close family members were asked about the age of start of permanent and progressive gait instability.…”
Section: Methodsmentioning
confidence: 99%
“…Oculomotor involvement is present at an early phase of SCA and is detectable even at premanifest stages as a higher rate of gaze-evoked nystagmus or other alterations, such as a square-wave jerk during central fixation, impaired vertical smooth pursuit, slow saccade, and a higher antisaccade error rate in SCA3 carriers than controls 13 , 38 , 39 . These alterations have been studied in detail in SCA2 patients, all of whom present specific oculomotor abnormalities (slow horizontal saccades up to saccade paresis) 40 .…”
Section: Biomarkersmentioning
confidence: 99%